EFISIENSI BANK UMUM SYARIAH DAN UNIT USAHA SYARIAH DI INDONESIA TAHUN 2012-2016 METODE NON PARAMETRIK - Linda Dwi Wahyu Putri; Atina Shofawati (Jurnal Ekonomi Syariah Teori dan Terapan, 2018)
This research purpose to analyze and comparing the level of efficiency of IslamicBanks and Sharia Business Unit in Indonesia. Input variables that used for measurement of efficiency are total of funds, fixed assets, and operational expenses, and output variables are total financing, cash, and other operational expenses. The method that used for measurement of efficiency is non parametric method with Constan Return to Scale (CRS) and Variable Return to Scale (VRS) assumption. The statistical tool that used for comparing the level of financing efficiency between Islamic Banks and Sharia Bussiness Unit is Mann-Whitney U-Test. The samples are 11 Islamic Banks and 19 Sharia Business Unit that comply with the specified sample criteria. The results of this researchshowed that with assumption CRS is Business Unit more efficient than Islamic Banks Islamic, but with assumption VRS is Islamic Banks more efficient than Business Unit. The result of hypothesis test showed that with CRS assumption there is a difference in level of efficiency of Islamic Banks and Sharia Business Unit in Indonesia, and with VRS assumption there is not difference in level of efficiency of Islamic Banks and Sharia Business Unit in Indonesia.  REFERENCESAmirillah, Afif. 2014. Efisiensi Perbankan Syariah Di Indonesia, JEJAK Journal of Economics and Policy, 7 (2): 100-202Arifin, Zainul. 2005. Dasar-Dasar Manajemen Bank Syariah. Jakarta: Pustaka AlvabetCharnes, W.V., Cooper and E. Rhodes. 1978. Measuring The Efficiency of Decision Making Units. North-Holland Publishing Company European, Journal of Operation Research.Vol. 2. Pp 429-444Hadad M., Wimboh, dan Dhaniel I. 2003. Analisis Efisiensi Industry Perbankan Indonesia: Penggunaan Metode Nonparametrik Data Envelopment Analysis (DEA). Buletin Ekonomi dan Perbankan, Vol. 1 (17), pp 1-28Harahap, Sofyan S., Wiroso dan Muhammad Yusuf. 2006. Akuntansi Perbankan Syariah. Jakarta: LPFE Usakti.Huri, Mumu Daman dan Indah Susilowati. 2004. Pengukuran Efisiensi Relatif Emiten Perbankan dengan Metode Data Envelopment Analysis (Studi Kasus: Bank-Bank yang Terdaftar di Bursa Efek Jakarta Tahun 2002). Jurnal Dinamika Pembangunan (Jdp), Volume 1 (2). Pp. 95-110.Ikatan Bankir Indonesia. 2014. Memahami Bisnis Bank Syariah. Jakarta: PT Gramedia  Kamaruddin, dkk. 2008. Asseing Production Efficiency of Islamic Banks and Conventional Bank Islamic windows in Malaysia. International Journal of Business and Mangement Science, Vol 1 (1), hal 31-48.Kamus BI-Bank Sentral Republik Indonesia (http://www.mediabpr.com/kamus-bisnis-bank/unit_usaha_syariah.aspx) diakses tanggal 19 Februari 2017.Kuncoro, Mudrajad. 2002. Manajemen Perbankan Teori dan Aplikasi. Yogyakarta: BPEE Muhammad. 2004. Manajemen Dana Bank Syariah. Yogyakarta: EKONISIAMuharam, Harjum dan Rizki Pusvitasari. 2007. Analisis Perbandingan efisiensi Bank Syariah di Indonesia dengan metode Data Envelopment Analysis periode 2005. Jurnal Ekonomi dan Bisnis Islam, Vol 2 No 3.Mokhtar, dkk. 2008. Efficiency and Competition of Islamic Banking in Malaysia. Humanomics, 24(1), 28-48.Otoritas Jasa Keuangan. 2016. Statistik Perbankan Syariah Desember 2016. (www.ojk.go.id, diakses 22 April 2017)Quran dan Terjemahannya. 2013. Kementerian Agama RI dengan Transliterasi Arab-Latin.Sari, Ditta Feicyllia. 2015. Analisis Pembiayaan Bank Umum Syariah Dan Bank Umum Konvensional Di Indonesia Dengan Metode Data Envelopment Analysis (DEA). Skripsi tidak diterbitkan. Fakultas Ekonomi dan Bisnis. Universitas Airlangga.Sholihin, Ahmad. 2010. Buku Pintar, Ekonomi Syariah. Jakarta: PT Gramedia Pustaka UtamaSiamat, Dahlan. 2004. Manajemen Lembaga Keuangan: Edisi keempat. Jakarta: Lembaga Penerbitan Fakultas Ekonomi Universitas Indonesia.Syafe’I, Rachmat. 2000. AL-HADIS (Aqidah, Akhlaq, Sosial, dan Hukum). Edisi Revisi, Hal 194. Bandung : CV PUSTAKA SETIA.UNAIR. 2009. Pedoman Peulisan Pembimbingan dan Ujian Skripsi. Surabaya: Fakultas Ekonomi dan Bisnis Universitas Airlangga.Undang-Undang Republik Indonesia. 2008. Undang-Undang Republik Indonesia Nomor 21 Tahun 2008 Tentang Perbankan Syariah.